A sulfur-containing polymer-plasticized poly(ethylene oxide)-based electrolyte enables highly effective lithium dendrite suppression. Issue 28 (6th July 2022) - Chen, Zhenying; Li, Jingyan; Qiu, Feng; Lu, Chenbao; Zhu, Jinhui; Zhuang, Xiaodong
Abstract : Herein, a multifunctional S-containing polymer filler to enhance PEO-based composite polymer electrolyte is reported. Abstract : Composite polymer electrolytes (CPEs) for practical all-solid-state Li-metal batteries require both high ionic conductivity and a stable interface with Li metal anode. However, current CPEs with functional fillers cannot balance these two requirements at the same time. Herein, we report a multifunctional S-containing polymer (SCP) as filler to effectively enhance poly(ethylene oxide) (PEO)-based CPEs. On one hand, our soluble SCP can be used as a plasticizer to improve the Li + transference number and ionic conductivity of the resulting CPEs; on the other hand, such a SCP can facilitate the formation of abundant Li2 S and LiF in the solid-electrolyte interphase layer to suppress the Li dendrite. In addition, such a SCP can act as an active material to swallow the penetrated Li dendrite and dead Li. Benefiting from these advantages, the as-prepared CPE paired Li|Li cell can run for nearly 1000 h, and the Li|LiFePO4 cell can deliver an initial specific capacity of 158 mA h g −1 at 0.2C, and exhibit a capacity retention of 109 mA h g −1 after 1000 cycles at 1C. This work provides a strategy to fabricate favorable CPEs with high ionic conductivity and the ability for effective Li dendrite suppression.